Demand and offer in the sunflower market in Ukraine - Sharkovska, S. (Land Management, Cadastre and Land Monitoring, 2018)
Abstract. Ukraine is one of the world’s largest producers and exporters of sunflower seeds and products for its processing. The current harvest of this oil crop will not be the same as last year, and therefore Ukraine can strengthen its position on the world market. At the same time, the dependence of domestic producers and processors on world market conditions will increase. Sunflower is considered to be one of the few crops that is in high demand both on the domestic and foreign markets, and allows agricultural enterprises to receive high profits. Sunflower seeds are used as valuable food products and are widely used by various industries in the processing industry. Sunflower seeds have a steady demand in different periods of the year, indicating its high liquidity and export attractiveness. In order to ensure the growth of sunflower seed production, the concentration of crops in the regions with the most favorable conditions is of great importance, therefore, the production of sunflower has been one of the most profitable agricultural enterprises in the last few years. Sunflower has become a traditional culture for modern agrarian business in Ukraine. This was facilitated by the stable demand of foreign markets for sunflower oil. As a result, attractive domestic market prices for sunflower seeds contributed to the expansion of sown areas and the introduction of modern technologies for its cultivation. Keywords. Market, production, demand, supply, price, profitability, oil crops.